ANALISIS KEBERHASILAN PROGRAM PENDAMPINGAN PENGEMBANGAN PRODUK UMM BAKERY METODE FROZEN DAN SOURDOUGH SEBAGAI UPAYA MENINGKATKAN UMUR SIMPAN DAN EFISIENSI PRODUKSI ROTI DI UMM BAKERY - Putri, Desiana Nuriza; Windiana, Livia; Mardhiyah, Nadia (Universitas Islam Balitar, 2019)
The development of the era changed the lifestyle and tastes of people to food, one of which bread that has now become food processed that often consumed by society. Increasing public interest in the consumption of bread leads to increased interest in business in the field of bakery. UMM Bakery as one of the business units in the field of bread and cake production commits the manufacture of its products do not use chemical preservatives. The use of chemical preservatives is what causes UMM Bakery products have a shelf life that is not long. Abundant orders also cause a lack of efficiency of human resources due to the swelling of the production costs of the cost of energy added. UMM Bakery Product Development Program in the form of dough making type sourdough and Frozendough become the right alternative to be applied. Sourdough can be a solution to overcome the use of commercial yeast into natural yeast that can later increase the shelf life and create a distinctive flavor of the product. Frozen dough method is also appropriately applied to increase energy efficiency in bread production to avoid swelling of production costs and maintain the quality of the product remains good.